Spontaneously appearing discrete moving kinks in nonlinear acoustic chain with realistic potential - Metlov, L.S.; Eremeichenkova, Yu.V. (Condensed Matter Physics, 2003)
Molecular dynamic simulations are performed to investigate a long-time evolution of different initial signals in nonlinear acoustic chains with realistic Exp-6 potential and with power potentials. First, in the chain with realistic potential, long-lifetime kink-shaped excitations are found in the system in thermodynamic equilibrium. They give sharp peaks on high-energy tile of Gibbs distribution. Travelling along the chain, each kink collects the energy from the background atoms, and, consequently, transfers it to smallamplitude phonons. Dynamic equilibrium is observed between the processes of growth and decay of the kinks.